IMPACT OF MARKETING PERSPECTIVE ON PROFITABILITY OF BROILER POULTRY INDUSTRY – A MODERATION ANALYSIS (International Journal of Food and Nutritional Sciences, 2022)
The main goal of the study is to understand the marketing perspective of broiler poultry industry. The study also aims towards understanding the marketing aspects impact on the profitability of the broiler firms using moderation analysis. Both primary and secondary data are included in the data collection. Examination of the information utilised by the marketing channel design. Using a combination of interview techniques and a prepared list of questions, primary data is gathered from farmers chosen as samples. Scientific publications and literature are sources of secondary data.